Strategy to Increase the Availability and Accessibility of Funds for AIDS, Tuberculosis and Malaria (ATM) Programs in Indonesia: Literature Review - Azizah, Siti Nurul; Septiana, Wulan; Widyastuty, Theresia Miranda; Azzahra, Raisya Shafa; Wasir, Riswandy (Universitas Ibn Khaldun Bogor, 2024)
This literature review explores Indonesia's strategies to enhance funding accessibility for AIDS, Tuberculosis, and Malaria (ATM) programs, with a focus on its collaboration with the Global Fund (GF). It outlines the critical role of funding in combating ATM and Indonesia's extensive health diplomacy efforts with the GF. Utilizing a systematic review approach, findings from four studies between 2019 and 2024 were synthesized. Results reveal varied findings, including challenges in TB treatment services during the COVID-19 pandemic, deficiencies in TB Multi Drug Resistant (MDR) control programs, and insights into Indonesia's partnership with the GF. The analysis of HIV/AIDS expenditure highlights a decline in funding, emphasizing the need for advocacy and revised funding mechanisms. In conclusion, Indonesia's efforts in ATM combat through health diplomacy, notably with the GF, are substantial. Diversified funding sources, sustained collaboration, and increased self-sufficiency are crucial for meeting global health targets. Strengthening domestic resources, optimizing program implementation, and fostering partnerships are imperative to ensure equitable access to healthcare services and sustain progress in addressing ATM challenges. Innovative financing mechanisms can bolster initiatives, contributing significantly to achieving Sustainable Development Goals (SDGs) by 2030.